2015
DOI: 10.1016/j.bone.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

RANK/RANKL/OPG pathway: Genetic associations with stress fracture period prevalence in elite athletes

Abstract: Context: The RANK/RANKL/OPG signalling pathway is important in the regulation of bone turnover, with single nucleotide polymorphisms (SNPs) in genes within this pathway associated with bone phenotypic adaptations.Objective: To determine whether four SNPs associated with genes in the RANK/RANKL/OPG signalling pathway were associated with stress fracture injury in elite athletes.Design, Participants, and Methods: Radiologically confirmed stress fracture history was reported in 518 elite athletes, forming the Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Mechanical loading is associated with increased bone mineral density,20 thus, runners with greater training volumes should, theoretically, have higher bone mineral density. Although ORs could not computed from mean data, bone density in runners with a history of stress fracture was lower than those without stress fractures, yet greater than that of non-athletes 10.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical loading is associated with increased bone mineral density,20 thus, runners with greater training volumes should, theoretically, have higher bone mineral density. Although ORs could not computed from mean data, bone density in runners with a history of stress fracture was lower than those without stress fractures, yet greater than that of non-athletes 10.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, lower lumbar spine BMD [28] and an increased risk of fracture have been shown [18]. The rs1718119 polymorphism results in increased receptor functioning related to monocyte activation and increases interleukin-1 alpha and beta release (32) 107 (30) 31 (33) 99 (31) from monocytes and macrophages [33]. Recent in vivo studies have shown that the rs1718119 variant may also be related to bone phenotypes, including increased BMD in middle aged (≥50 years) and osteoporotic men and women [27,28] and a reduced susceptibility to vertebral fracture in post-menopausal women and osteoporotic men and women [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the low number of female subjects, the male athletes were stratified into a male only cohort and cases of multiple stress fractures (more than one discrete occurrence at any site) for the purposes of analyses. Information on the SFEA cohort has been reported previously [31]. Ethical approval was granted by the Nottingham Trent University Ethical Review Committee, and each participant provided written informed consent prior to their involvement in the study.…”
Section: Elite Athlete Participantsmentioning
confidence: 99%
“…Stress fracture susceptibility, in relation to genetics, has also been investigated in athletes for the first time recently, with findings suggesting that athletes with specific genetic variants may have an increased vulnerability to this injury (Varley et al 2015, 2016, 2017). Interestingly, three of the same SNPs ( VDR FokI rs2228570, TNFSF11 rs1021188 and the loss of function P2RX7 rs3751143) as mentioned above, alongside TNFRSF11A rs3018362, were associated with stress fracture incidence in the Stress Fracture in Elite Athlete (SFEA) cohort.…”
Section: Genetic Association With Bmdmentioning
confidence: 99%
“…For example, higher total BMD in weight-bearing athletes than controls was observed in the FF (7.7%) and Ff (6.9%) but not ff (1.8%) genotypes of the vitamin D (1,25-dihydroxyvitamin D 3 ) receptor ( VDR ) FokI rs2228570 polymorphism, whilst lower total BMD was only observed in the FF (− 4.5%) genotype when comparing swimmers with a control group (Nakamura et al 2002b). Additionally, variants in the purinergic receptor P2X7 ( P2RX7 ), human TNF receptor superfamily member 11a ( TNFRSF11A ) and sclerostin ( SOST ) genes have been associated with stress fracture in elite athletes (Varley et al 2015, 2016, 2017). Substantial further study is needed on candidate genes associated with BMD and other phenotypes such as stress fracture, as well as greater exploration of genes that may interact with physical activity and the implications this would have for BMD and wider application in public health and elite sport.…”
Section: Introductionmentioning
confidence: 99%